Elite Sports Schools: An International Review - Radtke, S.; Coalter, F. (2007)
1 Sports schools: policy and practice 1.1 Introduction 1.2 The schools 1.2.1 Numbers and funding.. 1.2.2 Degree of integration 1.2.3 Flexible curricula 1.2.4 Academic records 1.2.5 Drop out rates 1.3 Sporting issues 1.3.1 Selection process 1.3.2 Number of sports 1.3.3 Partnerships 1.3.4 Coaching 1.3.5 Assessment of sporting performance 1.4 Conclusions 2 Australia 3 Belgium 4 Canada 5 Finland 6 France 7 Germany 8 Italy 9 Netherlands 10 Singapore 11 Sweden